Why Are Barnacles Common on Intertidal Rocks but Rare in Rock Pools? Effect of Water Temperature, Salinity, and Continuous Submergence on Barnacle Survival in Indian Ocean Rock Pools - Buasakaew, Nutcha; Chan, Benny K. K.; Wangkulangkul, Kringpaka (Frontiers in Marine Science, 2021)
Barnacles are less common in rock pools of the rocky intertidal zone than on open rock surfaces adjacent to those pools. Rock pools on the Andaman coastlines of Thailand showed diurnal variations in water temperature, salinity, pH and dissolved oxygen level, peaking in the afternoon. Multivariate analysis showed that water temperature and salinity (not pH and dissolved oxygen) can affect barnacle abundance in rock pools. The present study tests the hypothesis that a lack of recruitment or pool environmental conditions (continuous submergence, water temperature and salinity extremes) affect the abundance of barnacles (Chthamalus malayensis and Amphibalanus amphitrite) in rock pools. During the recruitment season, recruits were found in a number of rock pools, but at significantly lower abundances than those in adjacent open rock surfaces. In a laboratory experiment, C. malayensis and A. amphitrite that were continuously submerged had a lower survival (80%) than the controls (simulated tide conditions; >90% survivals). Under different water temperature and salinities treatments, barnacles had low survival (< 50 %) in the low salinity (0o/oo) and high temperature treatment (40C). The present study suggests that C. malayensis and A. amphitrite can recruit into rock pools, and the interplay of continuous submergence, high water temperature and low salinity in rock pools can bring about mortality in barnacles.